Surrogacy in Ukraine: theoretical and applied problem - V.S. Blikhar; I.M. Zharovska; N.V. Ortynska (Publishing House TRILIST, 2021)
The article analyzes the Ukrainian experience of carrying out the procedure of surrogacy. The modern world does not stand still constant progress in all spheres of human activity has given rise to a large number of new rights that have entered the fourth generation of human rights. Surrogacy belongs to the newest generation of human rights, despite the fact that it has a long history of its origin and development, which can be traced back to biblical texts, the laws of King Hammurabi and others. The use of another woman's womb was acceptable for couples who could not conceive their own child. It clearly illustrates the existence of surrogacy, which has more than 3,800 years. The article analyzes the progressive development of modern technology of IVF, which has opened new opportunities for humanity in case of infertility to have biologically native children. The main problems that exist in the research institute, which are related to each participant of the procedure, are highlighted. The analysis of foreign judicial practice is carried out, which allows to form certain conclusions that will have practical application in domestic realities. The legal regulation of surrogacy is considered, the need to change the age requirement for a surrogate mother and the requirements for the presence of a native child for the future surrogate mother are emphasized. Today, this institution is of particular importance to humanity, as there are many cases of infertility among couples who want to have a child and surrogacy becomes the only chance for them to have a biologically native child. The urgency of the outlined topic is intensified due to the fact that Ukraine has become a real center of surrogacy due to the availability of the procedure and loyal legislation, which allows for an altruistic and commercial form of its conduct. However, the low level of regulation of surrogacy has had a negative impact at all stages of the procedure and needs immediate improvement in order to preserve the interests of each participant, but above all, the child born with this method of assisted reproductive technology. The importance of all the issues outlined is also intensified in connection with the coronavirus pandemic, which has brought many problems into the research institute.